Integrated Flexible Ga2O3 Deep UV Photodetectors Powered by Environmental Electromagnetic Radiation Energy. Issue 3 (8th February 2021) - Wang, Tao; Liang, Huili; Han, Zuyin; Sui, Yanxin; Mei, Zengxia
Abstract: This work reports an integrated flexible deep ultraviolet (UV) photodetection system hosting an amorphous Ga2 O3 (a‐Ga2 O3 ) photodetector (PD) and an energy harvesting component including a receiving electrode and a full‐wave rectifier. An alternating signal is induced by the coupling of human body with environmental electromagnetic radiation through human hand's contact with the receiving electrode. The signal is subsequently converted into direct current (DC) by the rectifier which is composed of four thin‐film diodes with high rectification ratio (≈10 6 ) and fast response time (rising time ≈240 µs and falling time ≈680 µs). Driven by the DC output, the a‐Ga2 O3 PD achieves a photoresponsivity of 0.10 A W −1 and a detectivity of 2.24 × 10 11 Jones under 254 nm UV illumination. The integrated flexible a‐Ga2 O3 UV PD manifests a repeatable and pleasurable response behavior with a bending radius of 15 mm, providing a new paradigm for utilizing the environmental energy as the power source in wearable electronics. Abstract : A flexible self‐powered deep UV photodetector (PD) is constructed consisting of a receiving electrode, a full‐wave bridge rectifier, and an amorphous Ga2 O3 PD. By creatively utilizing the environmental energy through human body coupling, the integrated PD demonstrates light‐to‐dark ratio, responsivity, and detectivity of 8.31, 0.1 A W −1, and 2.24 × 10 11 Jones, respectively.